The Amphoteric Ion Exchange Membrane Based on CS/CMC for Tobacco-Protein Adsorption and Separation from Tobacco Extract - Jun Ling; Yixiao Li; Bo Zhou; Baokun Zhu; Xinru Zhang; Yonghong Wang; Tiandong Zhang; Wanying Feng (International Journal of Polymer Science)
A macroporous amphoteric ion exchange membrane was prepared by blending chitosan (CS) and carboxymethylcellulose (CMC) in aqueous solution, with glutaraldehyde as a crosslinking agent and silica particles as porogens. The good compatibility between CS and CMC was confirmed by attenuated total reflectance Fourier-transform infrared spectroscopy (FTIR-ATR). A scanning electron microscope was used to observe the morphology of CS/CMC blend membranes, in which a three-dimensional opening structure was formed, and no phase separation was discovered. Tobacco extract was used as a separation model to get tobacco protein. And the effects of the pH value, adsorption time, CS/CMC content, initial protein concentration, and CS/CMC composition on tobacco protein adsorption were investigated by coomassie blue staining during the adsorption process. The results showed that the maximum adsorption capacity of 271.78 mg/g can be achieved under the condition of pH 6.15, adsorption time of 8 h, initial protein concentration of 1.52 mg/mL, and CS/CMC weight of 0.05 g with a mass ratio of 80 : 20. Tobacco proteins were successfully separated from tobacco extract by adjusting the pH of the feed and the desorption solutions to change their electrostatic force. It was found that the high desorption capacity and protein desorption efficiency can be achieved at pH 9.40. The blend membranes also demonstrated good reusability after 3 adsorption-desorption cycles.